Epidemiological factors associated with the absence of previous HIV testing among HIV-positive persons in Singapore, 2012–2017 - Chen Seong Wong; Angela Chow; Li Wei Ang; Yee Sin Leo; Matthias Paul Han Sim Toh; Sophia Archuleta; Vernon Lee; Irving Charles Boudville (BMJ Open)
Objective To assess the temporal trend and identify risk factors associated with the absence of previous HIV testing prior to their diagnosis among HIV-positive persons in Singapore.Study design Cross-sectional.Setting and participants We analysed data of HIV-positive persons infected via sexual transmission, who were notified to the National HIV Registry in 2012–2017.Outcomes Epidemiological factors associated with the absence of HIV testing prior to diagnosis were determined separately for two groups of HIV-positive persons: early and late stages of HIV infection at diagnosis.Results 2188 HIV-positive persons with information on HIV testing history and CD4 cell count were included in the study. The median age at HIV diagnosis was 40 years (IQR 30–51). Nearly half (45.1%) had never been tested for HIV prior to their diagnosis. The most common reason cited for no previous HIV testing was ‘not necessary to test’ (73.7%). The proportion diagnosed at late-stage HIV infection was significantly higher among HIV-positive persons who had never been tested for HIV (63.9%) compared with those who had undergone previous HIV tests (29.0%). Common risk factors associated with no previous HIV testing in multivariable logistic regression analysis stratified by stage of HIV infection were: older age at HIV diagnosis, lower educational level, detection via medical care and HIV infection via heterosexual transmission. In the stratified analysis for persons diagnosed at early-stage of HIV infection, in addition to the four risk factors, women and those of Malay ethnicity were also less likely to have previous HIV testing prior to their diagnosis.Conclusion Targeted prevention efforts and strategies are needed to raise the level of awareness of HIV/AIDS and to encourage early and regular screening among the at-risk groups by making HIV testing more accessible.